2017
DOI: 10.3389/fmicb.2017.00513
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Aerotolerant Forms of a Robust Chicken Colonizing Campylobacter coli

Abstract: Campylobacter contaminated poultry meat is a major source of human foodborne illness. Campylobacter coli strain OR12 is a robust colonizer of chickens that was previously shown to outcompete and displace other Campylobacter strains from the chicken’s gastrointestinal tract. This strain is capable of aerobic growth on blood agar. Serial aerobic passage increased this aerotolerance as assessed by quantitative assays for growth and survival on solid media. Aerotolerance was also associated with increased peroxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 68 publications
1
22
1
Order By: Relevance
“…Survival in harsh environments might be a result of various factors and also dependent on the specific genomic background. In aerotolerant C. coli point mutations were detected in other genes, not obviously implicated in oxidative stress response 48 . Thus, it remains elusive, how Campylobacter species modulate their gene pool in order to adapt to changing environments.…”
Section: Discussionmentioning
confidence: 99%
“…Survival in harsh environments might be a result of various factors and also dependent on the specific genomic background. In aerotolerant C. coli point mutations were detected in other genes, not obviously implicated in oxidative stress response 48 . Thus, it remains elusive, how Campylobacter species modulate their gene pool in order to adapt to changing environments.…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions at 2113 site were found in our isolates. Based on previous reports and the sequenced reference strains, including C. jejuni NCTC 11168 and C. coli OR12 (Parkhill et al, 2000;Perez-Boto et al, 2010;O'Kane and Connerton, 2017), the dominant nucleotide at 2113 site is "C" in C. jejuni and "T" in C. coli, which were defined as wild type in both species in this study. Correlation analysis showed that this substitution was not correlated with erythromycin resistance (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter is an important foodborne pathogen that is transmitted from contaminated food products and water (Newell et al, 2017). Despite being microaerophilic and fastidious organism, many previous reports have reported the isolation of aerotolerant Campylobacter strains that could survive and grow in aerobic conditions (Rodrigues et al, 2015; Oh et al, 2017; O'Kane and Connerton, 2017). In our study, 46.7% (78/167) of tested Campylobacter strains were aerotolerant.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of complete genome sequences for C. coli and C. jejuni from both retail meat and liver products (Marasini and Fakhr, 2016a,b,c, 2017a,b,c) has facilitated comparative genomic analyses. Furthermore, genomic differences in C. coli and C. jejuni strains (Fouts et al, 2005) might help to explain differences in aerotolerance (O'Kane and Connerton, 2017).…”
Section: Introductionmentioning
confidence: 99%